Aging effects on the resting state motor network and interlimb coordination. Issue 8 (22nd January 2014) - Solesio‐Jofre, Elena; Serbruyns, Leen; Woolley, Daniel G.; Mantini, Dante; Beets, Iseult A. M.; Swinnen, Stephan P.
Abstract Both increases and decreases in resting state functional connectivity have been previously observed within the motor network during aging. Moreover, the relationship between altered functional connectivity and age‐related declines in bimanual coordination remains unclear. Here, we explored the developmental dynamics of the resting brain within a task‐specific motor network in a sample of 128 healthy participants, aged 18–80 years. We found that age‐related increases in functional connectivity between interhemispheric dorsal and ventral premotor areas were associated with poorer performance on a novel bimanual visuomotor task. Additionally, a control analysis performed on the default mode network confirmed that our age‐related increases in functional connectivity were specific to the motor system. Our findings suggest that increases in functional connectivity within the resting state motor network with aging reflect a loss of functional specialization that may not only occur in the active brain but also in the resting brain. Hum Brain Mapp 35:3945–3961, 2014. © 2014 Wiley Periodicals, Inc.